Radiocesium transfer from hillslopes to the Pacific Ocean after the Fukushima Nuclear Power Plant accident: A review - Evrard, Olivier; Laceby, J. Patrick; Lepage, Hugo; Onda, Yuichi; Cerdan, Olivier; Ayrault, Sophie (Journal of environmental radioactivity, 2015)
The devastating tsunami triggered by the Great East Japan Earthquake on March 11, 2011 inundated the Fukushima Dai-ichi Nuclear Power Plant (FDNPP) resulting in a loss of cooling and a series of explosions releasing the largest quantity of radioactive material into the atmosphere since the Chernobyl nuclear accident. Although 80% of the radionuclides from this accidental release were transported over the Pacific Ocean, 20% were deposited over Japanese coastal catchments that are subject to frequent typhoons. Among the radioisotopes released during the FDNPP accident, radiocesium (134Cs and 137Cs) is considered the most serious current and future health risk for the local population. The goal of this review is to synthesize research relevant to the transfer of FDNPP derived radiocesium from hillslopes to the Pacific Ocean. After radiocesium fallout deposition on vegetation and soils, the contamination may remain stored in forest canopies, in vegetative litter on the ground, or in the soil. Once radiocesium contacts soil, it is quickly and almost irreversibly bound to fine soil particles. The kinetic energy of raindrops instigates the displacement of soil particles, and their bound radiocesium, which may be mobilized and transported with overland flow. Soil erosion is one of the main processes transferring particle-bound radiocesium from hillslopes through rivers and streams, and ultimately to the Pacific Ocean. Accordingly this review will summarize results regarding the fundamental processes and dynamics that govern radiocesium transfer from hillslopes to the Pacific Ocean published in the literature within the first four years after the FDNPP accident. The majority of radiocesium is reported to be transported in the particulate fraction, attached to fine particles. The contribution of the dissolved fraction to radiocesium migration is only relevant in base flows and is hypothesized to decline over time. Owing to the hydro-meteorological context of the Fukushima region, the most significant transfer of particulate-bound radiocesium occurs during major rainfall and runoff events (e.g. typhoons and spring snowmelt). There may be radiocesium storage within catchments in forests, floodplains and even within hillslopes that may be remobilized and contaminate downstream areas, even areas that did not receive fallout or may have been decontaminated. Overall this review demonstrates that characterizing the different mechanisms and factors driving radiocesium transfer is important. In particular, the review determined that quantifying the remaining catchment radiocesium inventory allows for a relative comparison of radiocesium transfer research from hillslope to catchment scales. Further, owing to the variety of mechanisms and factors, a transdisciplinary approach is required involving geomorphologists, hydrologists, soil and forestry scientists, and mathematical modellers to comprehensively quantify radiocesium transfers and dynamics. Characterizing radiocesium transfers from hillslopes to the Pacific Ocean is necessary for ongoing decontamination and management interventions with the objective of reducing the gamma radiation exposure to the local population. [Display omitted] •The majority of radiocesium is transported in the particulate fraction.•The contribution of the dissolved fraction is only relevant in base flows.•Significant transfer of particulate-bound radiocesium occurs during heavy rainfall.•Radiocesium deposited in floodplains may be remobilized, inducing contamination.•Transdisciplinary approach is required to quantify radiocesium transfers.